Report of the Coke-Oven Projects Enquiry Committee - Planning Commission (Planning Commission, 1955)
The Government of West Bengal, on examination of the several possibilities for providing increasing opportunities for employment within the State, visualised the establishment at Durgapur of a Coke-oven Plant equipped for the recovery of various by-products therefrom and by 1953 obtained a preliminary report from Dr. C. Otto & Comp. of Germany. This proposal also contemplated the construction of a gas pipe line from Durgapur to Calcutta for supplying gas for industrial and domestic purposes at reasonable prices at Calcutta and other places. The by-product recovery and processing plants planned along with the coke-ovens have been regarded by the State Government as the nucleus of a coal-based chemical industry.
Government of India Planning Commission